2018
DOI: 10.12988/ces.2018.85217
|View full text |Cite
|
Sign up to set email alerts
|

BIM integration into railway projects - case study

Abstract: The technology of Building Information Modeling BIM is booming. More and more countries are introducing regulations to integrate BIM into new infrastructure projects. But this remains a tool designed initially for buildings, circumscribed geographically. Railway infrastructure projects are generally linear and extend over a line, with bifurcations. This article aims to confirm the theoretical results (benefits, limitations, risks) concerning the integration of BIM (Building Information Modeling) to railway pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Our work has shown several limitations: lack of feedback, lack of adaptability and convergence of tools, lack of maturity on railway projects that have implemented BIM. These limitations are similar to those found in the literature (Singh et al, 2011;Bensalah et al, 2018b), but they are accentuated in the rail because of the delay in the use of BIM.…”
Section: Oncf Electrical Substation Moroccosupporting
confidence: 89%
See 2 more Smart Citations
“…Our work has shown several limitations: lack of feedback, lack of adaptability and convergence of tools, lack of maturity on railway projects that have implemented BIM. These limitations are similar to those found in the literature (Singh et al, 2011;Bensalah et al, 2018b), but they are accentuated in the rail because of the delay in the use of BIM.…”
Section: Oncf Electrical Substation Moroccosupporting
confidence: 89%
“…Concerning this last point, we will discuss examples of regulatory frameworks (norms, legislations, etc. ) or their absence, feedback from four projects in different countries (realized after 2014) and a project in Morocco (Bensalah et al, 2018b). In the end, we will discuss the results and conclude on future research.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the guideline for collaboration was not clear and needed to be developed further. In 2018, Bensalah et al [12] implemented BIM in a railway project in Morocco. The results from their study confirmed the advantages and disadvantages of implementing BIM according to the literature.…”
Section: A Building Information Modeling (Bim)mentioning
confidence: 99%
“…}=at w =yC} Rt R= u=@]=Nt R= 55 'u; j@=]t xm 'OwW|t "OvOw@ `q]=|@ l}vwQDmr= \=@DQ= V}=Ri= 'l}vwQDmr= \=@DQ= |=yQ= R@= R= xO=iDU= |= Q@ xOW u=}@ |=yC}Rt QO "OvDUy p}qO =yu} QDsyt R= C}i}m <=kDQ= w C=]=@DQ= u=tR Vy=m 'Q=m s=Hv= CaQU xO=iDU= |= Q@ |DvU pt=wa `=vDt= w pt=wa |y=o ; u=Oki 'CaQUQB CvQDv}= Ow@v OQ=wt "OvDUy =yxOvvmCmQ=Wt Q_v R= ? }=at u} QDsyt R= 'l}vwQDmr= \=@DQ= |=yQ= R@= R= |=yQ= R@= R= xO=iDU= xm OyO|t u=Wv l}vwQDmr= \=@DQ= |= Q@ xOW u=}@ |=yC}Rt x@ QHD w Vv=O |Q=Pol= QDW= w xSwQB C} Q}Ot '= QH= C}i}m <=kDQ= x@ l}vwQDmr= \=@DQ= "Ov=xOQm O}} -=D = Q Q}N= ?r]t R}v [15] '2018 u= Q=mty w 17 KqYu@ xm 'Ovm|t ltm Q}_v |DvU |=y\=@DQ= ? }=at w =yC} Rt sWW p= -wU x@ =yMU=B '3 pmW QO #CU}J CN=U |=yx=oQ=m QO |Pe=m |Q=DWwv w |virD w wQ QO wQ |Q=Dio `q]= |DvU \=@DQ= ?…”
mentioning
confidence: 99%